Answer:
[tex]f_n=7+\left(-2\right)\left(n-1\right)[/tex]
Therefore, option C is true.
Step-by-step explanation:
From the graph, we get the sequence
7, 5, 3, 1, ...
Here,
a₁ = 7 is the first element.
An arithmetic sequence has a constant difference 'd' and is defined by
[tex]f_n=a_1+\left(n-1\right)d[/tex]
computing the differences of all the adjacent terms
[tex]5-7=-2,\:\quad \:3-5=-2,\:\quad \:1-3=-2[/tex]
The difference between all the adjacent terms is the same and equal to
[tex]d=-2[/tex]
substituting a₁ = 7 and d = -2 in the nth term of the sequence
[tex]f_n=a_1+\left(n-1\right)d[/tex]
[tex]f_n=7+\left(-2\right)\left(n-1\right)[/tex]
Therefore, option C is true.